The ketogenic diet as a potential therapeutic approach for migraine management: a review of current evidence - Bielecka, Larysa (Journal of Education, Health and Sport, 2024)
Introduction Migraine, a common neurological disorder, significantly reduces quality of life, particularly among women. Despite advancements in treatment, therapeutic options remain limited, and side effects are common. The ketogenic diet (KD), characterized by low carbohydrate and high fat intake, has shown promise in reducing migraine frequency and severity. Aim of the study The aim of this study is to review the literature on the effectiveness of of the ketogenic diet on the frequency of migraine attacks and their severity. Materials This review analyzed two studies by Di Lorenzo et al. (2018) and Caprio et al. (2023), both demonstrating that KD significantly reduced migraine days compared to non-ketogenic diets. Additional benefits included reduced inflammatory markers and improved body weight. Results While findings are promising, limitations such as small sample sizes, focus on overweight individuals, and lack of long-term safety data highlight the need for larger studies. Conclusions KD offers potential as an effective alternative for managing migraines, but further research is required to confirm its benefits and safety.